Penggunaan Model Regresi Untuk Prediksi Muka Air Tanah Gambut (Studi Kasus : Ogan Komering Ilir) - Rifandri, Danus; Sutikno, Sigit; Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
According to the peatland fire risk index, peat soils with a water table depth of more than 40 cm are at the very risk of land fires. Groundwater Level (GWL) plays an important role in determining the risk of fire. So that if changes in groundwater level in the future can be predicted, the risk of fire can also be minimized. The purpose of this study was to create a hydrological model to predict the depth of groundwater level (GWL) as a parameter of the potential for the fire to occur in peatlands using analysis. The data used for modeling are rainfall data and groundwater level data that have been recorded historically in peatlands with the installation of the SESAME tool at the study site. Regression analysis was carried out using four data length scenarios, namely 3 months, 6 months, 9 months, and 12 months to determine the periods that could represent hydrological conditions in the field. The results of the study resulted in a regression formulation for the prediction of the data length of 3 months, namely: Wn + 1 = Wn + 1,049 × R - (-0.0093 × Wn) + 0.0153, data length 6 months: Wn + 1 = Wn + 0.577 × R - (-0.0272 × Wn) + 0.0233, 9 months data length: Wn + 1 = Wn + 0.612 × R - (-0.0287 × Wn) + 0.0237, 12 months data length: Wn + 1 = Wn + 0.666×R - (-0.0248 × Wn) + 0.0229. Key words: regression models, groundwater level, peatland, peatlands fire, correlation value